2013
DOI: 10.1111/vru.12021
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic and Radiographic Characteristics of Aortic Lesions in 42 Dogs With Spirocercosis

Abstract: Spirocerca lupi is a common cause of vomiting, regurgitation, and sudden death in dogs that live in tropical or subtropical regions. Sudden death due to aortic rupture may occur with no preceding clinical signs. The purpose of this prospective study was to compare radiographic and computed tomographic (CT) characteristics of aortic lesions in a cohort of 42 dogs with endoscopically confirmed spirocercosis. Dorsoventral and right lateral recumbent thoracic radiographic findings were compared with pre- and postc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
1
14
1
2
Order By: Relevance
“…In human medicine, systemic hypertension has been implicated in causing aortic dilation, which can lead to aneurysm and dissection, but aortic aneurysm with or without dissection has been infrequently reported in the veterinary literature. Reports in the older literature and one more recent study describe cases with aneurysmal dilatation of the thoracic aorta associated with Spirocerca lupi . Echocardiographic identification of aortic aneurysm was found in one dog associated with systemic hypertension, and in another hypertensive dog presenting for posterior paresis with concurrent thoracic aortic dissection and abdominal aortic thromboembolism .…”
Section: Introductionmentioning
confidence: 87%
“…In human medicine, systemic hypertension has been implicated in causing aortic dilation, which can lead to aneurysm and dissection, but aortic aneurysm with or without dissection has been infrequently reported in the veterinary literature. Reports in the older literature and one more recent study describe cases with aneurysmal dilatation of the thoracic aorta associated with Spirocerca lupi . Echocardiographic identification of aortic aneurysm was found in one dog associated with systemic hypertension, and in another hypertensive dog presenting for posterior paresis with concurrent thoracic aortic dissection and abdominal aortic thromboembolism .…”
Section: Introductionmentioning
confidence: 87%
“…U ntil recently, CT applications for the thorax were mostly limited to morphologic evaluation of the chest wall, mediastinum, vessels, and lung parenchyma for differentiating normal from pathological conditions in companion animals . With the increased availability of multidetector‐row CT (MDCT) scanners with up to 320 detector rows that allow image acquisition with high temporal and spatial resolution, the utilization of this modality will likely rise for evaluating the thoracic cardiovascular system in companion animals and has been used in initial case reports and studies …”
Section: Introductionmentioning
confidence: 99%
“…Kok et al (2010) have shown that even in animals that responded positively to treatment for the prevention of oesophageal spirocercosis, damage to the thoracic aorta still occurred and could only be quantified during postmortem examination of the aorta. Kirberger et al (2013) have shown that computed tomographic and radiographic procedures can be used to detect aortic lesions but these are likely to be of value mainly when gross lesions are present. These results obtained during an experimental infection confirm those of Le Sueur et al (2010) who reported on the high efficacy of an imidacloprid 10 %/moxidectin 2.5 % spot-on to prevent infection with S. lupi in a large population of young dogs naturally exposed to S. lupi on Réunion Island.…”
Section: Discussionmentioning
confidence: 99%